1991
DOI: 10.3354/meps076195
|View full text |Cite
|
Sign up to set email alerts
|

Temporal change in foraging behaviour of the fish Coryphaenoides (Nematonurus) yaquinae in the central North Pacific

Abstract: Deep-sea grenadier fish Coryphaenoides (Nematonurus) yaquinae were attracted to a baited free-fall video camera and tracklng vehicle dunng 10 deployments in the central North Pacific (31°N, 159" W) at a depth of 5800 m. The mean time of arrival of the first fish was 31.0 min after landing on the sea floor. The mean number of fish within camera view increased to a peak of 5.25 at 90 min after landing and decreased thereafter The mitial arrival rate was 0.06 fish mm-', and mean fish staying time was 122 min The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Little is known of the life history of macrourids from the eastern North Pacific. A few common species of Coryphaenoides and Albatrossia pectoralis (Gilbert) have been studied (Novikov, 1970;Pearcy & Ambler, 1974;Stein & Pearcy, 1982;Wilson, 1982Wilson, , 1988Armstrong et al, 1991;Andrews et al, 1999;Buckley et al, 1999;Drazen et al, 2000) and scant ecological or biological information is available on eastern North Pacific species of Nezumia.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known of the life history of macrourids from the eastern North Pacific. A few common species of Coryphaenoides and Albatrossia pectoralis (Gilbert) have been studied (Novikov, 1970;Pearcy & Ambler, 1974;Stein & Pearcy, 1982;Wilson, 1982Wilson, , 1988Armstrong et al, 1991;Andrews et al, 1999;Buckley et al, 1999;Drazen et al, 2000) and scant ecological or biological information is available on eastern North Pacific species of Nezumia.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, seasonal variation in nutritional condition would result from changes in feeding activity, metabolism and growth. Seasonal variation in foraging behaviour has been described for both C. armatus (Priede et al, 1994) and C. yaquinae (Armstrong et al, 1991) and a pronounced seasonal input of organic matter to the deep-sea community is well documented at Station M Smith & Druffel, 1998). These investigators found that fishes had higher swimming speeds and shorter staying times at bait stations in autumn after the annual deposition of phytodetritus to the seabed.…”
Section: Discussionmentioning
confidence: 97%
“…Knowledge of seasonal cycles in their feeding activity is important for understanding the energetics of the species as well as defining their relationship with the rest of the community. Armstrong et al (1991) and Priede et al (1994) have shown that there is a seasonal variation in foraging behaviour (swimming speeds and staying times at artificial bait stations) for the macrourids Coryphaenoides yaquinae Iwamoto & Stein and Coryphaenoides armatus Hector in the central North Pacific and eastern North Pacific respectively. While these fishes are not eating phytodetritus, their prey populations could vary in abundance, activity or availability in response to phytodetritus input.…”
Section: Introductionmentioning
confidence: 99%
“…Grenadiers (Coryphaenoides yaquinae, C. armatus), deep sea eels (Synaphobranchus bathybius) and the deep sea gadoid (Antimora rostrata) have all been successfully tagged with acoustic tags after ingestion of bait hung beneath the cameras of a deep-sea lander (e.g. Armstrong et al, 1991Armstrong et al, , 1992aBagley et al, 1994;Priede et al, 1990Priede et al, , 1994aCollins et al, 1998).…”
Section: Demersal Fish and Shellfishmentioning
confidence: 99%